Synthesis and Characterization of Some New Nitrones Derivatives and Screening their Biological Activities - Mohammed, Jihad Haji; Mohammad Salih, Nabaz Abdulmajeed (Science Journal of University of Zakho, 2022)
Synthetic approached towards the synthesis of some novel nitrones derivatives have been started with reduction of nitrobenzene derivatives as starting material bearing electron withdrawing and electron donating groups to corresponding phenylhydroxylamine in presence of zinc dust as reducing agent in aqueous solution of ammonium chloride (NH4Cl). The prepared phenylhydroxylamine derivatives were reacted with different substituted benzaldehydes to give the target derivatives of nitrone. The structures of the synthesized nitrones were characterized by spectroscopic methods FT-IR, 1H-NMR and 13C NMR. Finally the newly synthesized compounds were screened for their microorganism activities at different concentration, and inhibited growth of Escherichia coli (E. coli) Gram negative, Staphylococcus aureus (S. aureus) Gram positive, and fungi (candida albicans).